2004
DOI: 10.3758/cabn.4.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Temporal kinetics of prefrontal modulation of the extrastriate cortex during visual attention

Abstract: Single-unit, event-related potential (ERP), and neuroimaging studies have implicated the prefrontal cortex (PFC) in top-down control of attention and working memory. We conducted an experiment in patients with unilateral PFC damage (n ϭ 8) to assess the temporal kinetics of PFC-extrastriate interactions during visual attention. Subjects alternated attention between the left and the right hemifields in successive runs while they detected target stimuli embedded in streams of repetitive task-irrelevant stimuli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 50 publications
8
45
1
Order By: Relevance
“…Thus, a pulse delivered at 150 ms after the cue, immediately preceding or coinciding with the onset of the gatingrelated ERP, would be more likely to have an interfering effect than one delivered at 200 ms, when the ERP has already peaked. These results are also consistent with single-cell studies (48)(49)(50) and other ERP studies (17,18,51,52) that have demonstrated the involvement of PFC in selecting behaviorally relevant information within the time frame of ∼150-200 ms after stimulus onset. predicted by models of a gating mechanism (21-23).…”
Section: Resultssupporting
confidence: 81%
“…Thus, a pulse delivered at 150 ms after the cue, immediately preceding or coinciding with the onset of the gatingrelated ERP, would be more likely to have an interfering effect than one delivered at 200 ms, when the ERP has already peaked. These results are also consistent with single-cell studies (48)(49)(50) and other ERP studies (17,18,51,52) that have demonstrated the involvement of PFC in selecting behaviorally relevant information within the time frame of ∼150-200 ms after stimulus onset. predicted by models of a gating mechanism (21-23).…”
Section: Resultssupporting
confidence: 81%
“…For example, early, extrastriate attention-sensitive components (P1 and N1) and novelty ERP responses are reduced in patients with lateral PFC lesions (Yago et al, 2004;Barcelo et al, 2000;Knight, 1997). Such a pattern was predicted and observed in the current study in LSES children.…”
Section: Discussionsupporting
confidence: 59%
“…The novelty N2 component reflects the automatic response to novelty (Knight, 1984;Courchesne et al, 1975), and it is dependent on a distributed novelty processing network with the PFC serving as a critical component of this system (Knight & Scabini, 1998;Knight, 1997). The early extrastriate P1 and N1 components and the novelty N2 have been shown to be reduced in patients with PFC lesions (Yago et al, 2004;Barcelo et al, 2000;Knight, 1984Knight, , 1997.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, event-related potentials studies (56,57) have repeatedly shown that humans can distinguish between the category of objects in scenes extremely rapidly, which we argue can be mediated by coarse LSF representations, and that this distinction is first apparent in prefrontal cortex time courses Ϸ150 ms from stimulus onset. That such prefrontal representations subsequently guide the activation of IT representations is supported by fMRI studies in human patients (9,58) and electrophysiology recordings in monkeys (10).…”
Section: Discussionmentioning
confidence: 68%